Binding and diffusion characteristics of 14C EDTA and 99mTc DTPA in respiratory tract mucus glycoprotein from patients with chronic bronchitis. Issue 9 (September 1988) - Cheema, M S; Groth, S; Marriott, C
Abstract : Measurement of pulmonary clearance of an inhaled aerosol of technetium-99m labelled diethylenetriaminepenta-acetate (DTPA) by external detection methods has been used widely as an index of permeability across alveolar epithelium and bronchial mucosa. To determine the applicability of the tracer to measurement of permeability in the airways the diffusion and binding characteristics of 99mTc DTPA and the chemically related ethylenediaminetetra-acetic acid labelled with carbon-14 (14C EDTA) was studied in purified respiratory tract mucus glycoprotein from patients with chronic bronchitis. The diffusion coefficients for 99mTc DTPA and 14C EDTA through mucus gels were significantly lower than those for tritiated water. Both molecules bound to the mucus gels with high affinity at two independent low capacity sites. Appreciable amounts of 99mTc DTPA or 14C EDTA are therefore unlikely to cross mucus layers of physiological thickness over periods of four or five hours. This suggests that when pulmonary clearance is determined by the 99mTc DTPA method the tracer retained in mucus lined airways will provide background activity. This study supports the assumption that pulmonary clearance measurements are mainly measuring alveolar epithelial permeability and should not be used to study bronchial epithelial permeability.